Vibrio gazogenes-dependent disruption of aflatoxin biosynthesis in Aspergillus flavus: the connection with endosomal uptake and hyphal morphogenesis - Jesmin, Rubaiya; Cary, Jeffrey W.; Lebar, Matthew D.; Majumdar, Rajtilak; Gummadidala, Phani M.; Dias, Travis; Chandler, Savannah; Basu, Paramita; Decho, Alan W.; Keller, Nancy P.; Chanda, Anindya (Frontiers in Microbiology, 2023)
Aflatoxins, a family of fungal secondary metabolites, are toxic and carcinogenic compounds that pose an enormous threat to global food safety and agricultural sustainability. Specifically agricultural products in African, Southeast Asian and hot and humid regions of American countries suffer most damage from aflatoxin producing molds due to the ideal climate conditions promoting their growth. Our recent studies suggest that Vibrio gazogenes (Vg), an estuarine bacterium non-pathogenic to plants and humans, can significantly inhibit aflatoxin biosynthesis in the producers. In this study, we investigated the mechanism underlying Vg-dependent aflatoxin inhibition using the prominent aflatoxin producer, Aspergillus flavus. We show that aflatoxin inhibition upon Vg treatment was associated with fungal uptake of Vg-prodigiosin, a red pigment, which was consistently visible inside fungal hyphae during treatment. The association of prodigiosin with aflatoxin inhibition was further evident as Serratia marcescens, another prodigiosin producer, significantly inhibited aflatoxin, while non-producers like Escherichia coli, Staphylococcus aureus, Vibrio harveyi, and Vibrio fischeri did not. Also, pure prodigiosin significantly inhibited aflatoxin biosynthesis. Endocytosis inhibitors, filipin and natamycin, reduced the Vg-prodigiosin uptake by the fungus leading to a significant increase in aflatoxin production, suggesting that uptake is endocytosis-dependent. The Vg treatment also reduced hyphal fusion (>98% inhibition) and branching, which are both endosome-dependent processes. Our results, therefore, collectively support our theory that Vg-associated aflatoxin inhibition is mediated by an endocytosis-dependent uptake of Vg-prodigiosin, which possibly leads to a disruption of normal endosomal functions.